Growing apart?: a tale of two republics: Estonia and Georgia - Thorvaldur Gylfason; Eduard Hochreiter (Center for Economic Studies and ifo Institute (CESifo), 2007)
We compare and contrast the economic growth performance of Estonia and Georgia since the collapse of the Soviet Union in 1991 in an attempt to understand better the extent to which the growth differential between the two countries can be traced to increased efficiency in the use of capital and other resources (intensive growth) as opposed to brute accumulation of capital (extensive growth). We infer that advances in education at all levels, good governance, and institutional reforms have played a more significant role in raising economic output and efficiency in Estonia than in Georgia which remains marred by various problems related to weak governance in the public and private spheres.
Keywords: O16; 330; economic growth; governance; transition economies; Wirtschaftswachstum; Governance-Ansatz; Estland; Georgien